Analisis Temuan Pemeriksaan BPK-RI atas Aset Tetap pada Laporan Keuangan Pemerintah Kabupaten Merangin, Pemerintah Kabupaten Tanjung Jabung Barat, Pemerintah Kabupaten Tanjung Jabung Timur pada Tahun Anggaran 2014 – 2016 - Toufan Sougi S; Sri Rahayu; Asep Machpuddin (Magister Ilmu Akuntansi Universitas Jambi, 2018)
Fixed assets are the largest components of a financial entity. The value of large fixed assets has a direct impact on risks in the entity's business finance process. The complexity of asset management, with all its derivative issues becoming an important issue in the transparency of state financial reporting. This study raises issues related to the findings of fixed assets, causes, and the development of follow-up. The purpose of this study is to find the main problem in the management of fixed assets, analyze the factors that affect the findings of fixed assets, and see the progress of the completion of the findings of fixed assets. The research was done by qualitative method, the technique of determining the data source used was purposive sampling, the data collecting was done by document analysis and in-depth interview with semi structured format. Data were analyzed by content analysis method, and data validity was tested by triangulation method. Keywords: Fixed Asset, Audit Findings, State Finance